Synchronous Acute Acalculous Cholecystitis and Appendicitis Due to Salmonella Group D: A Rare Case Report From China and Review of the Literature - Zhao, Yan; Zhang, Lijun; Xing, Fanfan; Zhang, Ruiping; Huang, Jinxian (Frontiers in Medicine, 2020)
Non-typhoidal Salmonella (NTS) disease is not common as typhoid fever, but has become a global public health problem in recent decades. Acute acalculous cholecystitis (AAC) and appendicitis are rare complications of NTS infection, which are usually difficult to be diagnosed with atypical signs. Pathogenesis of NTS-induced AAC and NTS-induced appendicitis is still unclear. Ultrasound (US) is the first choice for diagnosis of these two rare complications, computed tomography (CT) can be assistant, and next-generation sequencing (NGS), as a new technology in clinical medicine, also facilitates in diagnosis. We described a case of simultaneous AAC and appendicitis due to NTS in an elderly male and further confirmed the diagnosis using NGS. As far as we know, this is the first Asian case of two complications occurring at the same time. Our aim is to alert physicians to pay attention to this rare condition.